THE IMPACT OF ULTRAMILK SALES PROMOTION ON PURCHASE DECISION: (SURVEY ON STRAY KIDS FANS AT WHATSAPP COMMUNITY @SKZEVENT_JKT) - Septichia Kirani, Charrisa; Swarnawati, Aminah (Triwikrama: Jurnal Ilmu Sosial, 2025)
AbstractIn an increasingly competitive era, business actors need an effective marketing strategy in a competitive UHT milk industry to be able to influence consumer purchasing decisions. The purpose of this study was to determine Ultramilk sales promotions on Instagram social media, to determine purchasing decisions for Stray Kids fans in the WhatsApp Community @SKZevent_JKT, and to measure the effect of Ultramilk sales promotions on Instagram on purchasing decisions. This study uses a quantitative approach using a questionnaire as a data collection instrument. The theory used is Sales Promotion from Kotler and Keller (2019) and Purchasing Decision from Kotler and Keller (2019). The research sample consisted of Ultramilk consumers who joined the WhatsApp community @SKZevent_JKT with a population of 460 members. In this study, a sample of 82 respondents was taken using the Taro Yamane formula with a margin of error of 10%. The collected data were analyzed using simple linear regression analysis to test the relationship between the independent variable of sales promotion (X) and the dependent variable of purchasing decision (Y). The results showed that sales promotion had a partial effect on consumer purchasing decisions. These findings suggest that effective sales promotions can influence consumer purchasing decisions.Keywords: Sales Promotion, Purchasing Decision, Marketing Communication.